Type catalog from the fish collection of the Museu de Ciências Naturais, Fundação Zoobotânica do Rio Grande do Sul, Brazil - Bertaco, Vinicius A.; Azevedo, Marco A. (Zootaxa, 2018)
The catalog of type material deposited at the fish collection of the Museu de Ciências Naturais (MCN), Fundação Zoobotânica do Rio Grande do Sul, includes 315 specimens from 96 lots, representing six holotypes and 309 paratypes of 34 nominal species. Currently, two of them are synonymy and one have a questionable taxonomic status. Corrections and additional information from the original descriptions are included in the remarks for each species or lot. Photos of holotypes and paratypes are presented.